2018
DOI: 10.3390/cryst8070282
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Modelling and Hot Workability Analysis by Microstructure Examination of GH4169 Alloy

Abstract: The relationships between hot deformation parameters and flow behaviour have attracted many researchers' attention for the past few decades, whilst precise constitutive modelling of GH4169 remained a problem, which seriously affected the process and microstructure control of alloys. In this work, a modified Arrhenius type model was introduced to describe the flow stresses of various compression conditions. The model showed high precision in flow stress prediction. In order to facilitate workability evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In practical production of 300M steel forgings the optimal hot working parameters could be implemented by the deformation temperature selection, punch speed selection, and pre-forging shape designing. The optimal dissipation coefficient was between 35% and 40% according to previous research [26]. When the deformation temperature and the pre-forging shape was restrained, the punch speed curves could be continuously adjusted to ensure that the average dissipation coefficient was between 35% and 40%, and under such circumstances, the finite element simulation was beneficial for the optimization of punch speed curves.…”
Section: Hot Working Mapmentioning
confidence: 99%
“…In practical production of 300M steel forgings the optimal hot working parameters could be implemented by the deformation temperature selection, punch speed selection, and pre-forging shape designing. The optimal dissipation coefficient was between 35% and 40% according to previous research [26]. When the deformation temperature and the pre-forging shape was restrained, the punch speed curves could be continuously adjusted to ensure that the average dissipation coefficient was between 35% and 40%, and under such circumstances, the finite element simulation was beneficial for the optimization of punch speed curves.…”
Section: Hot Working Mapmentioning
confidence: 99%
“…Furthermore, more Σ3 twin boundaries were generated at a high strain rate. This is because the formation of Σ3 twin boundaries was promoted by DRX [23,24].…”
Section: Applicationmentioning
confidence: 99%
“…However, the Johnson-Cook model was inadequate for materials with nonexponential type stress-strain curves, and the Zerilli-Armstrong model was established for an NiTi alloy by Shamsolhodaei et al [3]. To achieve a higher prediction accuracy, the Arrhenius model was modified to incorporate the influence of strain, and based on the modified Arrhenius model, flow stress models were established for various nickel-based alloys, e.g., the GH4169 alloy by Chen et al [4], N08028 alloy by Wang et al [5], and 80A alloy by Gu et al [6]. The results by Lin et al [7] and Wang et al [8] indicated that the accuracy of the flow stress models could be further improved by a neural network, but the applications were limited, owing to the difficulty in finite elemental integration.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, physical-based models were proposed to investigate the underlying mechanisms of the influences of creep, dislocation motion, and grain size on flow stresses by Lin et al [9], Haan et al [10], and Zhou et al [11]. By comparing the above-mentioned models, the Arrhenius model showed an advantage in applicability and accuracy, and thus it has been widely used in the flow stress modeling of nickel-based alloys [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation